2022
DOI: 10.3389/fvets.2022.827599
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Confounding Factors on Liver Stiffness in Two-Dimensional Shear Wave Elastography in Beagle Dogs

Abstract: BackgroundTwo-dimensional shear wave elastography (2D-SWE) is a powerful technique that can non-invasively measure liver stiffness to assess hepatic fibrosis.PurposeThis study aimed to identify the effects of confounding factors, including anesthesia, breathing, and scanning approach, on liver stiffness when performing 2D-SWE in dogs.Materials and MethodsNine healthy Beagle dogs were included in this study. Hepatic 2D-SWE was performed, and liver stiffness was compared between conscious and anesthetized states… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…The results of the present study could not identify any statistically significant effect of sex on the SWV (P=0.39). Other canine studies (Cha et al, 2022;Jung et al, 2020;Tamura, Ohta, Nisa, et al, 2019) also failed to find an association with gender. However, the number of dogs in Holdsworth's et al study (2014) was small, and the difference could have resulted from the small sample size leading to type I error or natural variation between individuals.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The results of the present study could not identify any statistically significant effect of sex on the SWV (P=0.39). Other canine studies (Cha et al, 2022;Jung et al, 2020;Tamura, Ohta, Nisa, et al, 2019) also failed to find an association with gender. However, the number of dogs in Holdsworth's et al study (2014) was small, and the difference could have resulted from the small sample size leading to type I error or natural variation between individuals.…”
Section: Discussionmentioning
confidence: 91%
“…The appeal to use the non-invasive 2D SWE technique in veterinary medicine is clear; but similarly to human medicine, the impact of technical and patientrelated confounders have been conflicting (Cha et al, 2022;Facin et al, 2020;Holdsworth et al, 2014;Jung et al, 2020;K. Kim et al, 2020;Tamura, Ohta, Nisa, et al, 2019;Tamura, Ohta, Shimbo, et al, 2019) regarding approach (intercostal versus subxiphoidal), depth of ROI placement, breathing phase versus sedation/anesthesia, sex and body weight.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In human medicine, the intercostal approach is recommended as the highest intra–and interobserver agreement was obtained through that approach ( 20 ). One veterinary study in healthy Beagle dogs also showed a difference in liver elastography measurements according to approach ( 46 ), whereas another study with healthy Beagles did not find any correlation ( 25 ). Comparison of the outcomes between different studies is hindered as explained before; furthermore, while our method of recording velocities differentiates average, median, and maximum results, it is often not specified how the mean elastographic velocities in other studies are derived.…”
Section: Discussionmentioning
confidence: 99%